"HOME BASED EDUCATION" MODEL PENDIDIKAN BAGI ALTERNATIF ANAK-ANAK BAJO DAN NELAYAN - La Ode Muharam; Wa Ode Hijrah; Muhammad Aswar Limi (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2013)
Abstract: Home Based Education ModelAlternative Education for Bajo Children and Fisherman at Southeast Celebes. Purpose of this research and development was to create self learning materials for home based education (HBE) alternative education model for bajo children and fisherman at Wakatobi Region, Konawe, and Buton Southeast Celebes. The selected model was local content learning based on coastal environment packed in science education and social studies, which had purpose to introduce deeper in a variety shore ecosystem, coastal, and sea as for Bajo people. Through this kind of education they can guard, conserve, and use sea resources ecosystem in rational and responsible way for improving welfare and future of coastal children. The results showed the core of organized learning material of HBE comprised: (1) recognition of coastal environment, (2) conservation of coral reef, (3) conservation of natural resources, (4) care of coastal, shore, and sea ecosystem equilibrium, (5) conservation of rare and highly economic value sea biota.Abstrak: Penelitian pengembangan ini bertujuan menghasilkan bahan belajar mandiri (self learning materials) pada home based education (HBE) model pendidikan alternatif anak Bajo dan nelayan di Kabupaten Wakatobi, Konawe dan Buton Sulawesi Tenggara. Model yang dipilih adalah pembelajaran Muatan Lokal berbasis lingkungan pesisir yang dikemas dalam mata pelajaran IPA dan IPS, yang bertujuan untuk mengenalkan lebih mendalam berbagai ekosistem pantai, pesisir dan laut yang menjadi sumber pencaharian pokok masyarakat nelayan, khususnya orang-orang Bajo. Melalui pendidikan ini mereka diharapkan mampu menjaga, melestarikan dan memanfaatkan ekosistem sumberdaya laut secara rasional dan bertanggungjawab bagi peningkatan kesejakteraan dan masa depan anak-anak pesisir. Hasil penelitianya itu inti pokok peng¬organi¬sasian bahan belajar HBE terdiri dari: (1) mengenal lingkungan pesisir, (2) memeliharaterumbukarang, (3) konservasi sumberdaya hayati, (4) menjaga keseimbangan ekosistem pesisir, pantai dan laut, (5) melestarikan biota laut yang langka dan bernilai ekonomi tinggi.Kata Kunci: bahan belajar, home based education, anak Bajo, nelayan, sekolah dasar